Stabilising the global greenhouse: A simulation model - Peter Michaelis (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
This paper investigates the economic implications of a comprehensive approach to greenhouse policies that strives to stabilise the atmospheric concentration of greenhouse gases at an ecologicaliy determined threshold level. In a theoretical optimisation model conditions for an efficient allocation of abatement effort among pollutants and over time are derived. The model is empirically speeified and adapted to a dynamic GAMS-algorithm. By various Simulation runs for the period of 1990 to 2110, the economics of greenhouse gas aecumulation are explored. In particular, the long-run cost associated with the above stabilisation target are evaluated for three different policy scenarios: i) a comprehensive approach that covers all major greenhouse gases simultaneously, ii) a piecemeal approach that is limited to reducing CO2 emissions, and iii) a tenyear moratorium that postpones abatcment effort until new scientific cvidence on the greenhouse effect will become available. Comparing the Simulation results suggests that a piecemeal approach would considerably increase total cost, whercas a ten-year moratorium might be reasonable even if the probability of 'good news' is comparatively small.
Keywords: 330; Klimaveränderung; Luftverunreinigung; Kohlendioxid; Umweltpolitik; Wirkungsanalyse; Simulation; Welt